Trusteeship of an endowment in Islamic law: Theory and practice - Haji Abdullah, L. (2014)
Endowment in Islamic Law known as waqf or habs. In classical Islamic law, the jurists defined waqf as to devote the property in charity or family benefits in which the power of administration of the property is at the hand of the appointed administrator known in the law as nazir or mutawalli or in modern legal term known as trustee. Based on some prophetic injunctions the classical jurists developed significantly the roles of the trustee, his rights and responsibilities. It is admitted that there are very few prophetic injunctions that can be traced back to the time of the Prophet Muhammad but the classical jurists by virtue of their intellectual capacity have come out with rulings and interpretations in matters relating to the office of trustee. In Malaysia the law has provided that the trusteeship of the Muslims endowments vested in the hand of the state government which is parked under State Islamic Religious Council (SIRC). They are considered by law as the sole trustee of all the muslims endowments and they enjoy all the rights given by the law. This paper will explore this issue and aim to find tune between the classical Islamic law and the modern practice in relating to the trusteeship of endowments.